The Mediating Effects of IEAP on the Relationship Between General Cognitive Ability of Imamship and Masjid Performance in Lagos State, Nigeria - Eniafe, Abdulhadi Alade Tihamiyu; Azmin, Adi Anuar bin; Bin Abdullah, Shuhairimi (Li Falah: Journal of Islamic Economics and Business, 2021)
The purpose of this study is to examine the mediating effects of IEAP (Islamic ethical administrative practices) on the relationship between general cognitive ability (GCA) of Imamship and Masjid (mosque) Performance (MP) in Lagos State, Nigeria. This study utilized a quantitative approach. It employs a cross-sectional survey and administers 310 online questionnaires to the Chief Imams of central Masaajid (plural of a mosque/mosques) in Lagos State, Nigeria. The study used statistical techniques to analyze the collected data with partial least square structural - equation modelling - version 3 (PLS-SEM-V3). In the Lagos State of Nigeria, people have criticized the effectiveness of imams in theState. The critiques were raised based on the reason that the participation of Muslim Ummah in activities organized by imams is low. Ineffectiveness of imams this study aims to formulate the mediating effect of IEAP that will serve as the best administrative policy that can lead to a better management system in the Masjid to improve Masjid attendance and serve as an attraction for Muslims Ummah to come to the Masjid. The results of data on MP equally demonstrate that the Jama’ah would emulate their Chief Imams and consequently increase the performance of the Masaajid. This study recommends that with the presence of IEAP, the effectiveness of Chief Imam in promoting efficiency in MP by imbibing the knowledge/wisdom, truthfulness, responsibility/trust, and deliverance of Khutbah will increase. Finally, key benefits for practitioners and academia were discussed under the theoretical and practical contributions, while necessary suggestions for future study were recommended.